2022
DOI: 10.1186/s12886-022-02453-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of delayed follow-up due to COVID-19 lockdown on patients with neovascular age-related macular degeneration

Abstract: Background During the first wave of the coronavirus disease 2019 (COVID-19) pandemic in 2020 outpatient care of neovascular age-related macular degeneration (nAMD) patients was severely reduced due to lockdown. Missed visits are known to be detrimental to patients in need of continued anti-vascular endothelial growth factor (VEGF) intravitreal injections (IVIs). The purpose of the study was to assess the effect of a month-long pause of regular visits and anti-VEGF IVIs in nAMD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The BCVA and anatomical findings of the patients did not return to the pre-pandemic status even after 1 post-pandemic year, which is consistent with the results of previous studies [16,17]. However, these results should be interpreted with caution because patients with nAMD may exhibit a worsening long-term course despite receiving appropriate treatment during the follow-up period [18,19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The BCVA and anatomical findings of the patients did not return to the pre-pandemic status even after 1 post-pandemic year, which is consistent with the results of previous studies [16,17]. However, these results should be interpreted with caution because patients with nAMD may exhibit a worsening long-term course despite receiving appropriate treatment during the follow-up period [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have followed patients who experienced delayed treatment because of the pandemic for up to one year [16,17]. In these studies, it was reported that delayed treatment due to COVID-19 in nAMD patients resulted in impaired BCVA, which did not recover over the subsequent year.…”
Section: Introductionmentioning
confidence: 99%